Software as a Service (SaaS) as Cloud Computing: Security and Risk vs. Technological Complexity - Achar, Sandesh (Engineering International, 2016)
The software delivery model known as Software as a service (SaaS) has evolved from cutting-edge innovation to an essential technology for many companies. However, due to the extensive range of cloud services that companies offer as part of their SaaS offerings, it is indispensable to thoroughly comprehend the dangers associated with using these services. This article describes those dangers and recommendations for the most effective methods of control that are open to managers. This study’s objective is to investigate the factors of Technological Complexity, Security and Risk, and Technical Support within an organization to determine how these factors can influence an organization’s end-use intention regarding cloud technology. The availability of technical support, the complexity of use, and the organization’s training have been highlighted as the most crucial factors of this aim. The findings suggest that complexity negatively influences intention to use, although training and assistance are vital, with a similar weight. Shared or collective knowledge is essential in the adoption of cloud computing technologies.